EVALUASI MEDIA PEMBELAJARAN ARTICULATE STORYLINE DALAM PEMBELAJARAN FIQIH - Fajrul Falah; Evi Fatimatur Rusydiyah (Akademika, 2022)
Articulate Storyline learning media is a soft application that can be used for presentations. Articulate Storyline has the same advantages as Microsoft PowerPoint, also has various advantages can also create a very comprehensive and interesting presentation. This research aims to evaluate the use of Articulate Storyline Learning media, to identify the quality of Articulate Storyline media in fiqh learning. Research using a formative evaluation model, evaluation is carried out through 2 stages, namely: 1) review by media experts, and 2) review by material experts. Data collection techniques in the form of questionnaires, as well as data analysis techniques, are carried out through descriptive statistics with Likert scale measurement scales. The consequences of the review showed that the evaluation of Articulate Storyline learning media in fiqh learning is fitting to be utilized as a learning medium. Media excellence is evident from the results of its media experts = 80,43%, including the level of “ very good”. The overall research results of Articulate Storyline learning media are appropriate for use as a learning mechanism of fiqh learning.